Factors contributing to poor performance of internal auditing in public sector: A case study of Zanzibar Electricity Corporation (ZECO) - Mussa, Saleh Juma (Mzumbe University, 2024)
Dissertation Submitted in Partial/Fulfillment of the Requirements for the Award of Master of Science in Accounting and Finance (MSc) of Mzumbe University